Mechanistic Insights on Ternary Ni2−xCoxP for Hydrogen Evolution and Their Hybrids with Graphene as Highly Efficient and Robust Catalysts for Overall Water Splitting. (2nd August 2016) - Li, Jiayuan; Yan, Ming; Zhou, Xuemei; Huang, Zheng‐Qing; Xia, Zhaoming; Chang, Chun‐Ran; Ma, Yuanyuan; Qu, Yongquan
Abstract : Searching the high‐efficient, stable, and earth‐abundant electrocatalysts to replace the precious noble metals holds the promise for practical utilizations of hydrogen and oxygen evolution reactions (HER and OER). Here, a series of highly active and robust Co‐doped nickel phosphides (Ni2− x Co x P) catalysts and their hybrids with reduced graphene oxide (rGO) are developed as bifunctional catalysts for both HER and OER. The Co‐doping in Ni2 P and their hybridization with rGO effectively regulate the catalytic activity of the surface active sites, accelerate the charge transfer, and boost their superior catalytic activity. Density functional theory calculations show that the Co‐doped catalysts deliver the moderate trapping of atomic hydrogen and facile desorption of the generated H2 due to the H‐poisoned surface active sites of Ni2− x Co x P under the real catalytic process. Electrochemical measurements reveal the high HER efficiency and durability of the NiCoP/rGO hybrids in electrolytes with pH 0–14. Coupled with the remarkable and robust OER activity of the NiCoP/rGO hybrids, the practical utilization of the NiCoP/rGO‖NiCoP/rGO for overall water splitting yields a catalytic current density of 10 mA cm −2 at 1.59 V over 75 h without an obvious degradation and Faradic efficiency of ≈100% in a two‐electrode configuration and 1.0 m KOH. Abstract : Co‐doped nickel phosphide catalysts and their hybrids with reduced graphene oxide exhibit robust electrocatalytic activity toward both the hydrogen evolution reaction and the oxygen evolution reaction. Density functional theory calculations reveal that the Co chemical doping moderates trapping of atomic hydrogen and facile desorption of H2 when the most chemically active part of the surface is poisoned by hydrogen under the catalytic process.